Recent Advances in Costimulatory Blockade to Induce Immune Tolerance in Liver Transplantation - Ding, Mingjie; He, Yuting; Zhang, Shuijun; Guo, Wenzhi (Frontiers in Immunology, 2021)
Liver transplantation is an effective therapy for end-stage liver disease. However, most postoperative patients must take immunosuppressive drugs to prevent organ rejection. Interestingly, some transplant recipients have normal liver function and do not experience organ rejection after the withdrawal of immunosuppressive agents. This phenomenon, called immune tolerance, is the ultimate goal in clinical transplantation. Costimulatory molecules play important roles in T cell-mediated immune responses and the maintenance of T cell tolerance. Blocking costimulatory pathways can alter T cell responses and prolong graft survival. Better understanding of the roles of costimulatory molecules has facilitated the use of costimulatory blockade to effectively induce immune tolerance in animal transplantation models. In this article, we review the state of the art in costimulatory pathway blockade for the induction of immune tolerance in transplantation and its potential application prospects for liver transplantation.